Approaches in controllable generation of artificial pinning center in REBa2Cu3Oy-coated conductor for high-flux pinning. (30th August 2017) - Yoshida, Y; Miura, S; Tsuchiya, Y; Ichino, Y; Awaji, S; Matsumoto, K; Ichinose, A
Abstract: This paper reviews the progress of studies to determine optimum shapes of the artificial pinning center (APC) of REBa2 Cu3 O y thin films and coated conductors towards superconducting magnets operating at temperatures of 77 K or less. Superconducting properties vary depending on the kind and quantity of BaMO3 materials. Therefore, we study changes in the shapes of nanorods that are due to the difference in the quality of additives and growth temperature. In addition, we aim to control the APC using an optimum shape that matches the operating temperature. In particular, we describe the shape control of nanorods in SmBCO thin films and coated conductors by employing lower temperature growth (LTG) technology using seed layers. From the cross-sectional transmission electron microscopy observations, we confirmed that using the LTG method, the BaHfO3 (BHO) nanorods, which were comparatively thin and short in length, formed a firework structure in the case of SmBCO films with coated conductors. The superconducting properties in the magnetic field of the SmBCO-coated conductor with the optimum amount of BHO showed that F p max = 1.6 TN m −3 on a single crystalline substrate and 1.5 TN m −3 on metallic substrate with a biaxially textured MgO layer fabricated by ion-beam assisted deposition method tape 4.2 K.